Relationship Between Lesion Topology and Clinical Outcome in Anterior Circulation Large Vessel Occlusions. Issue 7 (July 2015) - Rangaraju, Srikant; Streib, Christopher; Aghaebrahim, Amin; Jadhav, Ashutosh; Frankel, Michael; Jovin, Tudor G.
Abstract : Background and Purpose—: Diffusion-weighted imaging (DWI) Alberta Stroke Program Early CT Score (ASPECTS), a surrogate of infarct volume, predicts outcome in anterior large vessel occlusion strokes. We aim to determine whether topological information captured by DWI ASPECTS contributes additional prognostic value. Methods—: Adults with intracranial internal carotid artery, M1 or M2 middle carotid artery occlusions who underwent endovascular therapy were included. The primary outcome measure was poor clinical outcome (3-month modified Rankin Scale score, 3–6). Prognostic value of the 10 DWI ASPECTS regions in predicting poor outcome was determined by multivariable logistic regression, controlling for final infarct volume, age, and laterality. Results—: Two hundred and thirteen patients (mean age, 66.1±14.5 years; median National Institutes of Health Stroke Scale, 15) were included. Inter-rater reliability was good for DWI ASPECTS (deep regions, κ=0.72; cortical regions, κ=0.63). All DWI ASPECTS regions with the exception of the putamen were significant predictors ( P <0.05) of poor outcome in univariate analyses. Statistical collinearity among ASPECTS regions was not observed. Using penalized multivariable logistic regression, only M4 (odds ratio, 2.82; 95% confidence interval, 1.39–5.76) and M6 (odds ratio, 2.45; 95% confidence interval, 1.15–5.3) involvement were associated with poor outcome. M6 involvement independently predicted poor outcome in right hemispheric strokes (odds ratio, 5.8; 95% confidence interval, 1.9–20.3), whereas M4 (odds ratio, 4.3; 95% confidence interval, 1.3–15.0) involvement predicted poor outcome in left hemispheric strokes adjusting for infarct volume. Topologic information modestly improved the predictive ability of a prognostic score that incorporates age, infarct volume, and hemorrhagic transformation. Conclusions—: Involvement of the right parieto-occipital (M6) and left superior frontal (M4) regions affect clinical outcome in anterior large vessel occlusions over and above the effect of infarct volume and should be considered during prognostication. Abstract : Supplemental Digital Content is available in the text.